ODL oh! ODL / Yong Azrina Ali Akbar and Wan Shahrul Aziah Wan Mahamad - Ali Akbar, Yong Azrina; Wan Mahamad, Wan Shahrul Aziah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
The pandemic of COVID-19 somehow has not come to its end yet even after almost 6 months of the struggles and brawls of the world combating this deadly virus. Since the end of December 2019 up to now, the world is struggling hard to lower the number of recorded cases in each country from time to time. COVID-19 is not only an issue of sustaining the best level of citizens' health status but also, an issue that is related to economics, well-being, education, and other aspects as well. On January 24, 2020, the first case of COVID-19 was recorded in Malaysia thus the World Health Organization Country Office in Malaysia has been working closely with the Ministry of Health to respond to this outbreak (WHO, 2020).